La subversion éthique contre l'ordre moral remarques sur la morale et la politique chez Levinas - Hayat, Pierre 1956- (2006)
Ethics presents itself to the modern subject as a responsibility confronted with history. In Levinas's philosophy of the "ethical subversion" one finds a radicalisation of this confrontation and a way to guard oneself against a conformist, hypocritical, and liberticidal moral order. Without misjudging the order of reason and politics, the hyperbolic development of ethics as initiated by Levinas allows us to rethink the freedom of the subject and to rediscover the amazement from which philosophy originates.
Keywords: Lévinas, Emmanuel -- 1906-1995; Ethik; Moral; Politik